Sugarloaf Land in south-eastern Brazil: a tropical hotspot of lowland inselberg plant diversity - de Paula, Luiza; Azevedo, Luísa; Mauad, Luana; Cardoso, Leandro; Braga, João Marcelo; Kollmann, Ludovic; Fraga, Claudio; Menini Neto, Luiz; Labiak, Paulo; Mello-Silva, Renato; Porembski, Stefan; Forzza, Rafaela (Biodiversity data journal, 2020)
Isolated monoliths of granitic and/or gneissic rock rising abruptly from the surrounding landscape are known as inselbergs. Dome-shaped inselbergs are common throughout the Atlantic Forest in south-eastern Brazil, a region known as Sugarloaf Land (SLL). This study aimed to create the first checklist of vascular plant species occurring on lowland inselbergs in SLL, with a focus on vegetation islands. We used information from online databases, our own field sampling and data from previously-published studies. We found 548 vascular plant species (505 angiosperms; 43 ferns and lycophytes) belonging to 69 families and 212 genera. Of all identified species, 536 are native and 12 are naturalised. We updated the information currently available in Flora do Brasil 2020, as 59% of the angiosperms and 63% of the ferns and lycophytes on our checklist were not previously characterised as occurring on rock outcrops. As a first step towards generating a Virtual Herbarium of lowland inselberg vascular plants, we added barcode vouchers with images available online for 75% of the total number of vascular species. In the official lists of endangered species, 115 angiosperms and five ferns and lycophytes are mentioned. However, the conservation status of many species have not yet been evaluated (77% angiosperms; 88% ferns and lycophytes), thus this list is an important step towards their conservation. The information provided herein is essential for management programmes related to rock outcrops in Brazil as they are facing serious threats to conservation.